PS-045 Analysis of medication use of frail elderly patients with frequent hospital admissions. (25th February 2017) - Cheong, VL; Silcock, J; Sowter, J; Hamilton, N
Abstract : Background: This descriptive analysis of medication prescribed for frail elderly patients with frequent hospital admissions is the first of such nature in this population group. Hospital readmission in the frail elderly is common and poses increased risks relating to medicines use and transition of care. Purpose: To describe the types of medication frequently admitted frail elderly patients are prescribed. Material and methods: This study was a retrospective cohort analysis of discharge summaries of 100 patients aged ≥75 years with ≥3 unplanned medical admissions in 12 months into the study site. Results: The mean number of admissions for these patients was 4.6 times a year (range 3–13). Of the 100 patients: 5% were taking <5 medications, 23% were taking between 5 and 9 medications, and 72% were taking ≥10 medications. The discharge summaries of the study population showed that 89% of the 100 patients were taking at least 1 high risk medicine 1 as regular medications. These high risk medicines were non-steroidal anti-inflammatory drugs (NSAIDs), antiplatelets, antiepileptics, hypoglycaemics, diuretics, inhaled corticosteroids, cardiac glycosides, beta-blockers and anticoagulants (including direct acting oral anticoagulants). The class of high risk medicines are outlined in the figure. Regular medication lists of the 100 patients were examined to identify any potentially inappropriate medicines (PIMs) in accordance with the Beers criteria. 48% of patients were found to be taking at least 1 PIM. The PIMs prescribed includes alpha-blocker, hypnotics, antipsychotics, tricyclic antidepressants and antimuscarinics, high dose diuretics and cardiac glycosides, and some antiarrhythmics (flecainide). This is not exhaustive as the PIM in certain medical conditions, as outlined by Beers criteria, was not assessed as clinical judgement could not be made from just looking at the discharge summary. Conclusion: A large proportion of frail elderly patients who had frequent hospital admissions were found to be taking high risk medicines and PIMs. This could facilitate targeted deprescribing of medicines in this patient population. References and/or acknowledgements: Howard RL, Avery AJ, Slavenburg S, et al. Which drugs cause preventable admissions to hospital? A systematic review. Br J Clin Pharmacol2007;63:136–47. No conflict of interest